Multi-Sensory Perception during Palpation in Japanese Midwifery Practice - Aug Nishizaka (Social Interaction, 2020)
This paper demonstrates ways in which vision is integrated with other modalities of perception in a manner relevant to a temporally unfolding activity. It will do so by analyzing a single episode extracted from an abdominal palpation conducted on a pregnant woman by a midwife in Japan. The episode forms a “natural experiment” through which one can demonstrate that the integrated visual and tactile perception of an object is organized differently according to the status of the ongoing activity in which it is embedded. Data are in Japanese with English translations.